Pengembangan LKPD Berbasis HOTS dalam Pembelajaran IPA Siswa SD Kelas V Tema 5 - Dwi Intan Juliana Fauziah; Arfilia Wijayanti; Ari Widyaningrum (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2021)
This study aims to determine the quality and feasibility of Student Worksheets (LKPD) based on Higher Order Thinking Skills (HOTS) in science learning. This type of research is development research. The development of this LKPD consists of seven stages, namely: (1) Potential and Problems, (2) Data Collection, (3) Product Design, (4) Design Validation, (5) Design Revision, (6) Product Trial, (7) Product Revision. The instruments used are product expert validation questionnaires, material expert validation questionnaires, teacher and student response questionnaires. The results of the research are from product expert validation testing as much as 97%, material experts as much as 96%. HOTS-based LKPD in science learning is declared to be of good quality for use in learning. The results of testing the quality and feasibility of the teacher and 20 students. Obtained from the teacher's questionnaire responses as much as 96%, student interest questionnaires as much as 97% of 20 students. In conclusion, the results of developing HOTS-based LKPD in science learning are declared feasible as learning aids at SD Negeri Pagejugan 03 Brebes.